SANKSI HUKUM TERHADAP LEMBAGA PERBANKAN YANG TIDAK MENDAFTARKAN JAMINAN FIDUSIA DALAM PRAKTIK PEMBIAYAAN KREDIT PEMILIKAN MOBIL (STUDI DI PT. BANK X) - Yosef Warmanto Panggabean; Tan Kamello; Edy Ikhsan; Utary Maharany Barus (USU LAW JOURNAL, 2018)
ABSTRACT The reason of the Banking Institution needs to register Fiduciary Guaranty in Car Ownership Credit Financing is to provide legal certainty to the interested parties. The most important factor not registered Fiduciary Guaranty is because the registration fee of fiduciary guarantee is too high causing the Debtor (Customer) Does not register its Fiduciary Guarantee, the finance company may be subject to sanctions in the form of warning, suspension of business activities, and revocation of business license.   Keywords : Sanctions, Warranties, Fiduciary, Banks